Econometric Methods for Evaluating of Open National Innovative Systems - Kudryavtseva, Svetlana S.; Shinkevich, Alexey I.; Pavlova, Adeliya V.; Chudnovskiy, Alexey D.; Nikolayeva, Aleksandra N.; Garipova, Gulnara R.; Doronina, Farida Kh.; Ishmuradova, Izida I. (International Journal of Economics and Financial Issues, 2016)
The urgency of the problem stated in the paper is reasoned by the fact that the rapid acceleration of the changes of the existing economic and institutional conditions raises the need to develop new theoretical-methodological and practical approaches to the problems' solving in order to achieve sustainable growth of innovation growth. The purpose of the paper is developing of a methodology to assess the open national innovation systems through the use of econometric models. The leading approach to the study of this problem is the method of economic-mathematical modeling, allowing evaluating of the level of national innovation systems' openness using quantitative indicators and building of innovative development's forecasts. The article reveals the essence of open innovations, open national innovation systems, on the basis of production functions the forecast of the share of service sector's value added in GDP is built using additive and multiplicative models. Paper Submissions are of theoretical and practical significance for open innovation management models' development, as well as for the development of the state innovation policy's strategy. Keywords: National Innovation System, Evaluation Methods, Econometric Modeling, Production Function, Additive Model, Multiplicative Model. JEL Classifications: B23, F41, O31